PENGARUH UKURAN DEWAN, PROPORSI WANITA DALAM DEWAN, KOMITE AUDIT TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MEDIASI (STUDI SUBSEKTOR PERBANKAN DI BURSA EFEK INDONESIA TAHUN 2012-2016) - Mangatas L, Maha Martabar; Efni, Yulia; Rokhmawati, Andewi (Jurnal Tepak Manajemen Bisnis, 2018)
Banking Industry use the Good Corporate Governance by the diversity(gender), and control to management, and a profesionalisme of Audit Committeeis a must so that the agency problem can be minimized, then the company can getthe profit and the sustainability.The aim of this research is to examine the effect ofBoard Size, Women on Board, and Audit Committee to Firm Value with FirmPerformance as mediating variabelThe population of this research is the listed bank on Indonesia StockExchange on year of 2012 to 2016. This paper examine 20 listed Indonesian StockExchanged Company by purphosive sampling methode for 5 years annual reportobservation.Using the Partial Least Square (PLS) approach, this paper show the resultthat Board Size has negatively non significant influence to Firm Performance andFirm Value, Women on Board is positively non significant influence to FirmPerformance and Firm Value, and Audit Committee is positively significantinfluence to Firm Performance and Firm Value. The implication of this researchis the necessary of GCG by diversity and transparency in Board room, byminimizing ageny conflict to maximizing the firm performance and firm value.